Rapid thermal reduced graphene oxide/Pt-TiO2 nanotube arrays for enhanced visible-light-driven photocatalytic reduction of CO2 - Sim, L.C.; Leong, K.H.; Saravanan, P.; Ibrahim, S. (2015)
In this study, a complicate natural photosynthesis process was prototyped through a photocatalysis process by reducing CO2 to light hydrocarbon, CH4. The composite photocatalyst employed for this study utilized Pt nanoparticles (Pt NPs) and rapid thermal reduced graphene oxide (RGO) deposited over the surface of the TiO2 nanotube arrays (TNTs). The existence and contribution of both Pt NPs and RGO in the composite was confirmed through various analytical techniques including XRD, HRTEM, FESEM, Raman, FTIR, XPS, UV-DRS and photoluminescence (PL) analysis. The TNTs in the composite exhibited pure anatase phase. The absorption bands at around 450 nm obtained from UV-DRS spectrum supported the existence of LSPR phenomenon of Pt NPs. The promising lower work function of RGO promoted the electrons transfer from TNTs to RGO efficiently. The successful depositions of Pt and RGO onto the surface of TNTs contributed for the improved photocatalytic activity (total CH4 yield of 10.96 mu mol m(-2)) in the reduction of CO2 over TNTs and Pt-TNTs. Both of RGO and Pt NPs are equally important to exert a significant impact on the improvement of CH4 production rates. (C) 2015 Elsevier B.V. All rights reserved.